IMPLEMENTASI SISTEM INFORMASI DAN PELAYANAN ADMINISTRASI KELURAHAN BERBASIS WEBSITE (STUDI KASUS: KELURAHAN TANJUNG) - Nadila Melati Sukma; Syarifuddin; Dahlan (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid development of information technology has encouraged government institutions to improve the quality of public services through the implementation of digital information systems. Tanjung Village continues to face various challenges in administrative services because most administrative processes are still performed manually, resulting in service delays, data recording errors, difficulties in document archiving, and limited public access to administrative information. This study aims to implement a website-based Village Information and Administrative Service System to enhance the effectiveness and efficiency of public services. The research employed the Research and Development (R&D) method using the Waterfall software development model, which consists of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using PHP as the programming language and MySQL as the database management system. The developed application provides features for population data management, online administrative letter submission, village information management, and administrative verification by village officers. The results indicate that all major system functions operated successfully based on Black Box Testing, demonstrating that the system effectively improves administrative service processes, simplifies data and document management, and enhances public access to village services. Therefore, the proposed system can support the digital transformation of village administration and serve as a reference for implementing similar systems in other villages.